Megameatus Intact Prepuce in a Two Years Old Boy in Katsina Northwestern Nigeria: A Case Report - Muhammad Ujudud Musa; Abdulkadir Abubakar; Sharfuddeen Abbas Mashi; Bashir Yunusa (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Megameatus Intact Prepuce (MIP) is a rare variant of glandular hypospadias that affects about 3-6 percent of hypospadias cases. Juskiewenski et al first described MIP in 1983, and Duckett and Keating described the pyramid procedure in 1989. In 2011, Elbatarny et al reported modified Glanular Approximation Procedure (GAP) for seventeen patients. Our patient was a 2-year-old boy who had an anomalous external urethral meatal orifice of 6cm in diameter, for which he received a successful modified glanular approximation procedure (GAP). Our patient underwent a modified Glanular Approximation Procedure (GAP) with excision of the redundant skin, as described by Elbatarny et al. (6), and we used a size 6 French Foleys catheter as a stent, as described by Gittes et al. We monitored our patient for six months with excellent results, as reported by Zaontz et al. and Gittes et al. Megameatus intact prepuce is a social emergency that must be addressed as soon as possible to avoid the catastrophic psychological effects that it can cause.